Penggunaan Evaluasi Diklat Model ROI Untuk Mengetahui Hasil Diklat Berdasarkan Cost-Benefit - Nurlaili, Zainab; Inayati, Mahfida; Nurhadi, Ali (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Evaluation is the most important thing in the implementation of training, because it reflects the level of development and progress in the quality of training results. Research methods are steps that have been systematically arranged to achieve the field of science. And the method used in this study is qualitative which is Library Research, which is research that combines library data in the form of books, journals, magazines, historical records and other literature literature. In this case, the researcher collects relevant data and then analyzes the data by reading carefully and writing it with a conclusion Evaluation of training in the ROI (return on investment) model or also known as Return on Training Investment/ROTI) is an evaluation that measures the benefits of training compared to the costs (cost-benefit). The ROI model introduces the training program evaluation stages which include 4 (four) main stages, namely: evaluation planning, data collection, data analysis, and reporting evaluation results